Pendampingan Pembukuan Digital Melalui Excel Akuntansi Dan Google Sheet Di UMKM Toko Parfum “X” - Feryansyah; Dina Amalya Putri; Nadia Nuril Ferdaus; Alfian Sayuti (Universitas Mataram, 2025)
This community service activity aims to enhance the capacity of MSME owners in conducting financial record-keeping through Digital Accounting Assistance using Accounting Excel and Google Sheets at Perfume Shop “X”. The assistance is carried out to help the business owner transition from inefficient manual bookkeeping to a more structured, accurate, and accessible digital bookkeeping system. The implementation methods include basic bookkeeping training, introduction to key features of Accounting Excel and Google Sheets, as well as hands-on practice based on actual transactions occurring in the shop. Through this practical mentoring process, the business owner is able to understand the financial recording workflow, operate digital bookkeeping templates, and independently prepare simple financial statements. The results show that the use of digital technology in bookkeeping can increase efficiency, minimize recording errors, and help MSME owners monitor their business’s financial condition more effectively. Overall, this community service activity successfully improved digital bookkeeping literacy and provided a positive impact on the financial management of the MSME.